A dynamic rescue route planning method based on 3D network in mine water inrush hazard. Issue 1 (1st January 2019) - Zhao, Xiangwei; Wang, Qingzhong; Xie, Bin; Pan, Shun; Ji, Min
Abstract: Water inrush in mine is one of the most common hazards in the mining industry. To solve the problem of rescue route planning during a mine water inrush hazard, a dynamic rescue route planning method based on a 3 D network is proposed. First, the basic elements in the 3 D network model of the mine roadway are abstractly described, furthermore, the weights of edges, the topological connectivity of the elements, and the data structure of the network are defined. Then, the Dijkstra algorithm and the Breadth-first search algorithm are combined to implement the best rescue search route and return route planning based on the 3 D network model. Finally, the dynamic rescue route planning is simulated in 3 D virtual spatial scenario of a real mine. The factors such as topological connectivity of the elements, real-time water level, and slope of the mine roadways are considered in the process of rescue route planning, as the rescue route is adjusted dynamically according to the actual situations. This method proposed can provide powerful decision support for mine water inrush hazard rescue.